PELAKSANAAN PEMBINAAN TERHADAP RESIDIVIS ANAK PADA LEMBAGA PEMBINAAN KHUSUS ANAK KLAS II TANJUNG PATI KABUPATEN LIMAPULUH KOTA - Yuserlina, Anny; Failin, Failin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Regulations regarding the education system specifically for school-age children at Special Child Development Institutions (LPKA), including in article 3 letter (n) of the Children's Criminal Justice System Law Number 11 of 2012 stipulate that every child in the criminal justice process has the right to receive education. Apart from that, Special Child Development Institutions are obliged to provide education, skills training, guidance and fulfill other rights in accordance with the provisions of the Legislative Regulations. This education and coaching program is supervised by the Correctional Center. One of the rights of child prisoners is to receive education and teaching. In Article 1 of the National Education System Law Number 20 of 2003, education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have spiritual, religious strength, self-control, personality, intelligence, noble character. , as well as the skills needed by himself, society, nation and state.Keywords: Implementation, Development, Education, Teaching, Development Institutions, Children